Psychological benefits of networking technologies in children's experience of ensemble music making. (February 2019) - Hanrahan, Fidelma; Hughes, Ed; Banerjee, Robin; Eldridge, Alice; Kiefer, Chris
Little is currently known about the possible benefits of using networked technology to enhance ensemble performance. This study explored whether the introduction of specially devised technology – networked tablets using traditional music notation – to a primary school orchestra would enhance the experience of ensemble music. Particular emphasis was placed on how the technology could help children to overcome practical problems associated with ensemble playing for early-stage musicians (e.g., keeping in sync with other players), thereby leading to better engagement with the music and ultimately greater enjoyment. Findings from a thematic analysis of responses from a focus group with eight young orchestra players aged 9–11 years and from an interview with the orchestra conductor, together with indications from the statistical analysis of 28 orchestra participants' questionnaire responses, suggest that the technology did help to reduce the practical problems associated with ensemble playing. This appeared to interrupt the downward spiral of frustration and lack of confidence in playing for some young people, and enhanced the likelihood of feelings of enjoyment and belonging.